Zmiany zawartości węgla organicznego oraz wzajemny stosunek jego form w rekultywowanych utworach po eksploatacji węgla brunatnego w rejonie Łęknicy = The changes in forms of organic carbon and its content in reclaimed area of Łęknica region - Śliwińska, Agnieszka; Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The samples were taken from the plots experiment established in the areas of the "Przyjaźń Narodów" lignite mine in Łęknica Region. The discussed land characterized very unfavorable physical-chemical properties chemiczne [Krzaklewski, Wójcik 2007, Greinert 1988, Greinert et al. 2009]. The mean soil samples taken from individual soil horizons were extracted by sodium hydroxide (Schnitzer method).
Keywords: nieużytki po kopalni węgla brunatnego; rekultywacja; węgiel organiczny; kwasy fuwowe i huminowe; land after brown coal-mine; reclamation; organic carbon; fulvic and humin acids